Identification of Chemical Components of Qi-Fu-Yin and Its Prototype Components and Metabolites in Rat Plasma and Cerebrospinal Fluid via UPLC-Q-TOF-MS. (28th December 2021) - Li, Hengyu; Zhao, Hongwei; Yang, Yong; Qi, Dongmei; Cheng, Xiaorui; Wang, Jiafeng
Abstract : Qi-Fu-Yin, a traditional Chinese medicine formula, has been used to treat Alzheimer's disease (AD, a neurodegenerative disorder) in clinical setting. In this study, the chemical components of Qi-Fu-Yin and its prototype components and metabolites in rat plasma and cerebrospinal fluid, after oral administration, were preliminarily characterized via ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS). A total of 180 compounds, including saponins, flavonoids, organic acids, sucrose esters, oligosaccharide esters, phthalides, phenylethanoid glycosides, alkaloids, xanthones, terpene lactones, ionones, and iridoid glycoside, were tentatively characterized. For the first time, 51 prototypical components and 26 metabolites, including saponins, phthalides, flavonoids, sucrose esters, organic acids, alkaloids, ionones, terpene lactones, iridoid glycoside, and their derivatives, have been tentatively identified in the plasma. Furthermore, 10 prototypical components (including butylidenephthalide, butylphthalide, 20(S)-ginsenoside Rh1, 20(R)-ginsenoside Rh1, and zingibroside R 1 ) and 6 metabolites were preliminarily characterized in cerebrospinal fluid. These results were beneficial to the discovery of the active components of Qi-Fu-Yin anti-AD.